THE EFFECT OF INVESTMENT KNOWLEDGE AND RISK PERCEPTION ON INVESTMENT INTENTION IN THE CAPITAL MARKET (STUDY ON LECTURERS AND STUDENTS AT FACULTY OF ECONOMICS AND BUSINESS SAM RATULANGI UNIVERSITY) - Meiva Meryam Baguna; Joy. E. Tulung; Lawren J. Rumokoy (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
The primary objectives of this research are threefold: firstly, to examine the Effect of Investment Knowledge on Investment Intention in The Capital Market (Study on Lecturers and Students at Faculty of Economics and Business Sam Ratulangi University); secondly, to assess The Effect of Risk Perception on Investment Intention in The Capital Market (Study on Lecturers and Students at Faculty of Economics and Business Sam Ratulangi University); and thirdly to explore the Effect of Investment Knowledge and Risk Perception on Investment Intention in The Capital Market (Study on Lecturers and Students at Faculty of Economics and Business Sam Ratulangi University). The research adopts a quantitative approach and involves 416 respondents consisting of lecturers and students at Facutly of Economics and Business Sam Ratulangi University. However, only 400 respondents meet the criteria and can be processed for further analysis. Multiple linear regression analysis, utilizing IBM SPSS Version 26 as the analytical tool, demonstrates that both Investment Knowledge and Risk Perception significantly affect Investment Intention, both simultaneously and partially.    Keywords: investment knowledge, risk perception, investment intention, capital market